Nuclear Security Risk Analysis: An Insider-Outsider Collusion Scenario - Mohammad A. Hawila; Sunil S. Chirayath (International Journal of Nuclear Security, 2016)
This study analyses the vulnerability of the physical protection system (PPS) deployed at a hypothetical facility. The PPS is designed to prevent and eliminate threats to nuclear materials and facilities. The analysis considers possible outsider and insider threats. A modified adversary sequence diagram (ASD) evaluates threat pathways to test an insider-outsider collusion case. The ASD also measures the probability of adversary interruption by demonstrating the methodology for a typical nuclear facility.
Keywords: physical protection system; insider threat; vulnerability analysis; security risk